SUBERMAN regulates developmental suberization of the Arabidopsis root endodermis - Cohen, Hagai; Fedyuk, Vadim; Wang, Chunhua; Wu, Shuang; Aharoni, Asaph (The Plant journal : for cell and molecular biology, 2020)
Summary Root endodermis, the innermost cortical layer surrounding the root vasculature, serves as the foremost barrier to water, solutes, and nutrients taken up from soil. Endodermis barrier functionality is achieved via its hydrophobic coating of lignified Casparian strips and the suberin lamellae; nonetheless the regulatory mechanisms underlying endodermis suberization are still elusive. Here, we discovered that the Arabidopsis SUBERMAN (SUB) transcription factor controls the establishment of the root suberin lamellae. Transient expression of SUB in Nicotiana benthamiana leaves resulted in the induction of heterologous suberin genes, the accumulation of suberin‐type monomers, and consequent deposition of suberin‐like lamellae. We demonstrate that SUB exerts its regulatory roles by transactivating promoters of suberin genes. In Arabidopsis, SUB is expressed in patchy and continuous suberization root endodermal cells, and thus roots with higher or lower expression of SUB display altered suberin polymer deposition patterns and modified composition. While these changes did not interfere with Casparian strip formation they had a substantial effect on root uptake capacity, resulting in varied root and leaf ionomic phenotypes. Gene expression profiling revealed that SUB function impacts transcriptional networks associated with suberin, phenylpropanoids, lignin, and cuticular lipid biosynthesis, as well as root transport activities, hormone signalling, and cell wall modification. Our findings highlight SUB as a regulator of root endodermis suberization during normal development, and its characterization is thus a key step towards dissecting the molecular mechanisms partaking in root endodermal barrier functionalities. Significance Statement The capacity of root endodermis to function as a successful barrier is achieved by the deposition of lignified Casparian strips and suberin lamellae in its cell walls during development. Here, we discovered that the Arabidopsis SUBERMAN (SUB) transcription factor controls establishment of the root suberin lamellae. Its characterization constitutes a key step towards dissecting the molecular mechanisms partaking in root endodermal barrier functionalities.